The Relationship between Health Education and Nurses' Compliance with Nursing Care Standards - Mardianti, Lina; Darmojo, Hardjito S (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2023)
Background: Nurses' adherence to nursing care standards is an important indicator in ensuring the quality and safety of healthcare services. Nursing care standards serve as professional guidelines for implementing a systematic and evidence-based nursing process. One factor suspected of influencing nurses' adherence is health education, both formal and continuing education through training and competency development. Objective: This study aims to analyze the relationship between health education and nurses' adherence to nursing care standards. Methods: This study used a quantitative analytical design with a cross-sectional approach. The study sample consisted of 225 nurses working in hospital inpatient units, selected using a purposive sampling technique. Data were collected through a structured questionnaire that measured the level of health education and nurses' adherence to nursing care standards. Data analysis was performed using the chi-square test and logistic regression with a significance level of p < 0.05. Results: The results showed a significant relationship between health education and nurses' adherence to nursing care standards (p = 0.001). Nurses with higher health education were more likely to adhere to nursing care standards than nurses with lower health education. Conclusion: Health education plays a significant role in improving nurses' adherence to nursing care standards. Strengthening continuing education and training is recommended as a strategy to improve the quality and safety of nursing services.